Motivating students for distance learning in the context of the Covid-19 pandemic. - Yekimov, Sergey; Danylovych, Oksana; Baidala, Viktoriya; Vasylieva, Larysa; Mikhailychenko, Oleh (My University, 2021)
Distance learning based on the use of telecommunications technologies allows not only to communicate with the use of a foreign language, but also to gain an understanding of foreign culture and history, but also to gain skills in the use of a foreign language in order to solve professional problems. By participating in telecommunications projects, students become more interested in actively participating in the educational process. Team creative activity of students aimed at solving various communication tasks increases, in our opinion, the motivation to acquire new knowledge and skills. In connection with the COVID-19 pandemic, students of many educational institutions were transferred to distance learning. From this point on, students could study some academic disciplines through the use of interactive technologies. However, the transition of all subjects to distance learning was an unpleasant surprise for many students. Teachers of the course of foreign languages for students of non-linguistic specialties began to note a decrease in student performance as a result of the transition to distance learning of foreign languages. We attribute this decrease to a decrease in students ' motivation to participate in the educational process. We suggested using the project method to increase motivation for distance learning of a foreign language. At the end of the academic semester, teachers who teach foreign languages for students of non-linguistic specialties noted the progress of the students ' reading skills in technical literature corresponding to their chosen profession.